Entropy Bottlenecks at T →0 in Ce-Lattice and Related Compounds - Sereni, Julian Gustavo Renzo (2015)
A number of specific heat (Formula presented.) anomalies are reported in Ce- and Yb-lattice compounds around 1 K which cannot be associated to usual phase transitions despite of their robust magnetic moments. Instead of a (Formula presented.) jump, these anomalies show coincident morphology: (i) a significant tail in (Formula presented.), with similar power law decay above their maxima ((Formula presented.)), (ii) whereas a (Formula presented.) dependence is observed below (Formula presented.). (iii) The comparison of their respective entropy gain (Formula presented.) indicates that (Formula presented.)ln2 is condensed within the (Formula presented.) tail, in coincidence with an exemplary spin-ice compound. Such amount of entropy arises from a significant increase of the density of low energy excitations, reflected in a divergent (Formula presented.) dependence. (iv) Many of their lattice structures present conditions for magnetic frustration. The origin of these anomalies can be attributed to an interplay between the divergent density of magnetic excitations at (Formula presented.) and the limited amount of degrees of freedom: (Formula presented.)ln2 for a doublet-ground state. Due to this “entropy bottleneck,” the paramagnetic minimum of energy blurs out and the system slides into an alternative minimum through a continuous transition. A relevant observation in these very heavy fermion systems is the possible existence of an upper limit for (Formula presented.)J/mol K(Formula presented.) observed in four Yb- and Pr-based compounds.